Paratesticular clear cell carcinoma of müllerian origin-A case report - Laura Warmke; David Vining; John Ward, III; Michelle Lin; Jae Y. Ro; Miao Zhang (Elsevier, 2020)
Ovarian epithelial-type tumors of the testis and paratestis are very rare, comprising <0.1% of testicular tumors. Among ovarian epithelial-type tumors, clear cell carcinoma of Müllerian origin is the least common subtype with very few cases reported in the literature. Herein we report the histologic features, immunohistochemical characteristics and aggressive clinical course of a primary clear cell carcinoma of Müllerian origin involving the paratestis and testicular parenchyma, arising in a 68-year-old patient. We show that the immunophenotypic features of this rare tumor are similar to its ovarian counterpart, demonstrating positivity for PAX8, HNF-1β and p504s. The positivity for HNF-1β and p504s is especially helpful as PAX8 positivity is present in metastatic clear cell renal cell carcinoma, one of the main diagnostic pitfalls. We also review other published cases to evaluate prognosis and treatment. Given the aggressive nature of this tumor, knowledge of this rare entity with early recognition is essential.